EPID-01. GLIOBLASTOMA TREATMENT OF BEVACIZUMAB ERA IN KANSAI REGION, JAPAN. Issue 11 (6th November 2017) - Mori, Kanji; Shofuda, Tomoko; Okita, Yoshiko; Arita, Hideyuki; Kinoshita, Manabu; Terakawa, Yuzo; Tsuyuguchi, Naohiro; Tomogane, Yusuke; Fukai, Junya; Ishibashi, Kenichi; Nishida, Namiko; Taki, Takuyu; et al.
Abstract: Randomized trials failed to prove the efficacy of Bevacizumab on OS of newly diagnosed glioblastomas, but improvement of PFS was revealed. Based on these results, Japanese national health insurance approved Bevacizumab (Bev) for both primary and recurrent glioblastoma treatment in 2013. And at same period, BCNU wafer was also able to be administered. The objective of this study was to examine the influence upon treatment of Glioblastoma that these new therapeutic modalities had, and to find the most popular treatment for glioblastomas in Kansai region, Japan. For this purpose, we retrospectively reviewed clinical data of 223 newly diagnosed glioblastoma patients which were collected for molecular biological analysis by Kansai Molecular Diagnosis Network for CNS Tumors between 2006 and 2016. We examined how treatments of glioblastoma altered after 2013. In 79 patients diagnosed before June 2013, 68 (86.1%) were received concomitant chemoradiotherapy (CCRT) with temozolomide (TMZ), three (3.8%) radiation therapy (RT) only, four (5.1%) chemotherapy (CMT) only, and four (5.1%) none. In 144 patients after that, 113 (78.5%) were received CCRT, six (4.2%) RT only, 19 (13.8%) CMT only, and six (4.2%)none. Bevacizumab was used for 29 patients (20.1%) at initial treatment, 21 (14.6%) at recurrence, and 13 (9.0%) throughout. That is, only about half of glioblastoma patients were treated with Bev. We also found that TMZ were still most frequently used for treatment after recurrence, and nitrosourea was not used at all since 2013. Significant alterations observed were increase of TMZ chemotherapy without RT and use of reduced radiation dose, which were mainly selected based on methylation status of MGMT promoter and patients' age. Finally, it seems that more personalized treatment for glioblastoma has been introducing in these days, but additional treatment resulting to improvement of prognosis has not become popular.